ASSET INVENTORY APPLICATION DESIGN FOR GEDE PANGRANGO VILLAGE LOCAL GOVERNMENT OF SUKABUMI REGENCY - Ridwan Ridwan; Indra Nanda; Fathia Rahma Khoerunisa (LP2M CBI Press, 2023)
Gede Pangrango Village, Kadudampit District, Sukabumi Regency is a government agency engaged in the community and village empowerment sector such as village development and village fund allocation. This community service activity is to design a local government asset inventory application so that the system running in this section can run more computerized. The development method uses the waterfall method, and system modeling uses a flow mapand Unified Modeling Language (UML) using the Dreamweaver programming language while the software tools used MySQL as the database. With the local government asset inventory application that we made, namely by maximizing more automated and more efficient computerization is used. So that officers or admins will be facilitated in the process of inputting data and in making reports and systems that are made using automation and a good data storage system. And it would be even better if the system created was developed to be even better in terms of appearance and the addition of other features, so that it would be able to cover all existing activities in Gede Pangrango Village, Kadudampit District, Sukabumi Regency.